Growth, physiological and biochemical variations in okra infected by root-knot nematode - Anukiran , S; Nayak, D K; Sujit , K B; Avanish , K S; Nishith , D (Plant Science Today, 2025)
Nematode infection causes significant change in the physiology of the plant. So, the study was conducted to investigate the impact of root knot nematode on okra. Six cultivars of okra were evaluated against root knot nematode; out of these, one was found to be resistant, two were moderately resistant and three were susceptible cultivars with the highest number of galls. In present study, the chlorophyll content of the susceptible cultivar was less than the moderately resistant and resistant cultivar. Maximum reduction was found in inoculated Utkal Gaurav 31.64 % as compared to Chota bana bhendi (18.44 %). In Chota bana bhendi, the chlorophyll b content was decreased from 5.4 to 4.6 mg/g of fresh leaf. Similarly, maximum reduction was seen in the case of susceptible cultivar Utkal Gaurav, i.e., 25.35 % and 22.34 % in Chota Bana Bhendi. The phenol content of inoculated roots of okra was increased by 15.40 %, 17.95 % and 34.91 % in cultivars Utkal Gaurav, Jhar bhendi and Chota bana bhendi respectively, over uninoculated plants. Whereas the proline content in roots of inoculated plants of okra was increased by 27.63 %, 21.51 % and 19.31 % in Utkal Gaurav, Jhar bhendi and Chota bana bhendi cultivars respectively. In all cultivars percentage macronutrient content significantly increased over the uninoculated plants, but the maximum increase recorded in Utkal gaurav shown Nitrogen (2.52 %), Phosphorus (1.6 %) and Potassium (3.43 %). The lowest concentration of Nitrogen (2.14 %) and Phosphorus (1.14 %) and Potassium (3.06 %) were observed in inoculated resistant cultivar. So, the identified resistant cultivar recommended for commercial cultivation.